Beyond the dominant discourse on internationalization of higher education - Fernanda Geremias Leal (Universidade Estadual de Campinas, 2021)
Research on internationalization of higher education has been predominantly non-theoretical and positivist rather driven towards the consecution of practical objectives than concerned with the structures in which internationalization operates, or its dilemmas and contradictions. Dr. Chrystal George Mwangi, an Associate Professor at the College of Education of the University of Massachusetts Amherst, United States, is one of the academic voices that has questioned the idea of internationalization as an 'unconditional good' as often emphasized by dominant political and academic discourses. In this interview, conducted in June 2020, Dr. George Mwangi reflects on internationalization of higher education from a critical approach, addressing issues such as the impact of choices on how to engage on this process; the challenges of being a scholar-practitioner in this field; and the role of internationalization in the Covid-19 pandemic context.